The Skinny on Being Narrow:: A Longitudinal Study on the Influence of Niche-Width in the Presence of Market Turbulence - Gaudes, Andrew (Journal of Comparative International Management)

(untitled) (Management Futures, 2004)
Abstract This study examines whether product specialization offers retailers greater performance in a period of market turbulence. Incumbent retailers of home improvement products were followed over six years (1995-2001) comprising a period before, during, and after a period of environmental turbulence generated by the entry of large format retailers Home Depot and Revy to the Winnipeg market. Data collection involved survey, interview, and observational methods of 58 participants. Niche width was operationalized using four different methods, yet no significant difference could be found in the performance of organizations that specialized or generalized in home improvement products. This finding goes against much of the cross-sectional research on product specialization and niche strategies in retail, underscoring the importance of longitudinal study in research on organizations.